2003
DOI: 10.1002/ca.10107
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion fracture of the pelvis: Separation of the secondary ossification center in the superior margin of the acetabulum

Abstract: A 13-year-old female sustained a rare avulsion fracture of the secondary ossification center in the superior margin of the acetabulum as the result of contraction of the reflected head of the rectus femoris muscle. Diagnosis was made from plain films and CT scans with 3D image reconstruction. The patient was treated non-operatively by bed rest with semiflexion of the hip and knee, and appropriate analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…1 However, recent radiologic studies using MRA have indicated that reflected head injuries may be more common. 1,5 It was shown that the reflected head of the rectus femoris blends with hip capsule on posterior coronal images and is closely associated with the acetabular labrum (Fig. 4 Adjacent structures such as the anterior hip capsule and labrum may be at risk for associated injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, recent radiologic studies using MRA have indicated that reflected head injuries may be more common. 1,5 It was shown that the reflected head of the rectus femoris blends with hip capsule on posterior coronal images and is closely associated with the acetabular labrum (Fig. 4 Adjacent structures such as the anterior hip capsule and labrum may be at risk for associated injury.…”
Section: Discussionmentioning
confidence: 99%
“…1 Injuries to this muscle is commonly seen in the pediatric population, specifically in adolescent athletes. 4,5 Given the anatomic location of the origin of the reflected head near structures, such as labrum, capsule, and acetabular cartilage, traumatic avulsions of the reflected head could be associated with concomitant injury to these structures. The direct head of the muscle arises from the anterior inferior iliac spine (AIIS) and the indirect or reflected head attaches to the superior acetabular ridge and often has fibers that insert onto the hip capsule.…”
mentioning
confidence: 99%
“…US confirms the diagnosis: the tendon is retracted, the avulsed fragment appears hyperechoic, with a posterior acoustic shadow (Figure ). IRF avulsion fractures are rare . US, which is less expensive and does not use ionizing radiation, should be preferred to CT.…”
Section: Pathologic Findingsmentioning
confidence: 99%
“…9 Fusion of these ossification centers are completed at approximately 15--17 years, 16 years and 18 years of age, respectively. 8,12 We report a rare case of an avulsion fracture involving the ASIS origin of the sartorius and osseous origins of both heads of the rectus femoris in an adult. 11 Injuries to the rectus femoris musclotendinous complex most often occur with the hip extended and the knee flexed.…”
Section: Introductionmentioning
confidence: 99%